2016
DOI: 10.1175/mwr-d-15-0445.1
|View full text |Cite
|
Sign up to set email alerts
|

All-Sky Microwave Radiance Assimilation in NCEP’s GSI Analysis System

Abstract: The capability of all-sky microwave radiance assimilation in the Gridpoint Statistical Interpolation (GSI) analysis system has been developed at the National Centers for Environmental Prediction (NCEP). This development effort required the adaptation of quality control, observation error assignment, bias correction, and background error covariance to all-sky conditions within the ensemble–variational (EnVar) framework. The assimilation of cloudy radiances from the Advanced Microwave Sounding Unit-A (AMSU-A) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 40 publications
4
93
2
Order By: Relevance
“…Radiance observations affected by cloud or precipitation have potentially more useful information than clear‐sky radiance observations. Currently, at most NWP centers, various forms of all‐sky radiance observations are assimilated [ Bauer et al ., ; Kazumori et al ., ; Zhu et al ., ], but all‐sky radiance assimilation has some limitations because of its complexity.…”
Section: Introductionmentioning
confidence: 79%
“…Radiance observations affected by cloud or precipitation have potentially more useful information than clear‐sky radiance observations. Currently, at most NWP centers, various forms of all‐sky radiance observations are assimilated [ Bauer et al ., ; Kazumori et al ., ; Zhu et al ., ], but all‐sky radiance assimilation has some limitations because of its complexity.…”
Section: Introductionmentioning
confidence: 79%
“…We note here that, by building on the above studies, it has been demonstrated that the direct assimilation of all‐sky MW and IR satellite radiances is now possible in principle. All‐sky MW data are considered easier to use than all‐sky IR data due to the smoother properties of the MW radiative transfer model output between cloudy and clear scenes (Bauer et al ., ), so these data were the first to be treated directly (Bauer et al ., ; Zhu et al ., ; Migliorini and Candy, ). Recently though, satellite IR data have also been assimilated directly (Zhang et al ., ; Minamide and Zhang, ; Okamoto et al ., ), which is discussed further in Sections 6.5, 6.8 and 6.9.…”
Section: Methods Of Assimilation Of Atmospheric Water Informationmentioning
confidence: 99%
“…More recently there have been successful studies showing how IR and MW satellite data can be assimilated in all-sky conditions using a number of direct assimilation methods. Studies include those of Minamide and Zhang (2018) and Okamoto et al (2019) for IR data, and Zhu et al (2016) and Migliorini and Candy (2019) for MW data. All of these studies have used some kind of observation error variance inflation scheme to account for errors due to the presence of cloud.…”
Section: Sensitivities Of Radiances To Cloud and Precipitation Fieldsmentioning
confidence: 99%
“…Satellite information has become one of the dominant sources for improving numerical weather prediction (NWP) model‐based forecasts. In the last few years, all‐sky satellite‐based microwave sounder data have shown great benefit to forecast improvement at operational NWP systems (Bauer et al, ; Geer et al, ; Zhu et al, ) and in the research community (Li et al, ; Yang et al, ; Zhang et al, ). Infrared (IR) radiances, however, are often not fed into the assimilation system because a large percentage of those data are contaminated with clouds (Eresmaa, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%